Advancing Sustainable Development through the lens of Energy Efficiency: A Systematic Literature Review - Aktar, Most. Asikha; Dhahi, Al-Amrani Khadeem Ali; Abdullahi, Usman (International Journal of Energy Economics and Policy, 2024)
The global focus on Sustainable Development (SD) encompasses social, economic, and environmental concerns. Energy efficiency plays a crucial role in this transition, defined as efforts to reduce energy consumption by lowering service demand. It is widely recognized as one of the most cost-effective, tested, and accessible strategies to achieve SD, fostering economic growth, social progress, and carbon reduction. To understand the interplay between energy efficiency and SD, a comprehensive review is needed. This study examines previous research on SD through the lens of energy efficiency, utilizing the SCOPUS database to select 46 publications from 2006 to 2022. These studies are categorized by year, publishers, journals, country, sectors, citations, data analysis methods, and sustainable dimensions. The classification helps identify gaps, such as the lack of a unified research framework. Advanced nations conducted 30.43% of the studies, with most research focusing more on environmental aspects than economic or social ones. This study expands the literature by highlighting connections between energy efficiency and SD, aiding scholars and practitioners in promoting sustainable development alongside energy efficiency. Consequently, the literature review focused on empirical research.